Molecular characterization and antibiotic resistance profiles of Salmonella isolated from fecal matter of domestic animals and animal products in Nairobi. Issue 1 (December 2017) - Nyabundi, Diana; Onkoba, Nyamongo; Kimathi, Rinter; Nyachieo, Atunga; Juma, Gerald; Kinyanjui, Peter; Kamau, Joseph
Abstract Background Salmonella has significant public health implications causing food borne and zoonotic diseases in humans. Treatment of infections due toSalmonella is becoming difficult due to emergence of drug resistant strains. There is therefore need to characterize the circulating non-typhoidalSalmonella (NTS) serovars in domestic animals and animal products in Kenya as well as determine their antibiotic resistance profiles. Methods A total of 740 fecal samples were collected from cows (n  = 150), pigs (n  = 182), chicken (n  = 191) and chicken eggs (n  = 217) from various markets and abattoirs in Nairobi. The prevalence of NTS serovars using culture techniques and biochemical tests, antimicrobial sensitivity testing using disc diffusion method of the commonly prescribed antibiotics and phylogenetic relationships using 16S rRNA were determined. Results The results showed that the overall prevalence ofSalmonella was 3.8, 3.6, 5.9 and 2.6% for pigs, chicken, eggs and cows respectively. Two serovars were isolatedS. Typhimurium (85%) andS. Enteritidis (15%) and these two serovars formed distinct clades on the phylogenetic tree. Forty percent of the isolates were resistant to one or more antibiotics. Conclusion The isolation ofSalmonella Typhimurium andSalmonella Enteritidis that are resistant to commonly used antibiotics from seemingly healthy animals and animal products poses a significant public health threat. This points to the need for regular surveillance to be carried out and the chain of transmission should be viewed to ascertain sources of contamination.